2004
DOI: 10.1038/sj.bjp.0705917
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase‐9 in human platelets: regulation of platelet activation in in vitro and in vivo studies

Abstract: 1 The aim of this study was to identify the presence of matrix metalloproteinase-9 (MMP-9) in human platelets and systematically examine its inhibitory mechanisms of platelet activation. 2 In this study, we report on an efficient method for the quantitative analysis of pro-MMP-9 in human platelets using capillary zone electrophoresis (CZE). To elucidate subcellular localization of MMP-9 in human platelets, we investigated intraplatelet MMP-9 by immunogold labeling and visualized it using electron microscopy. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 27 publications
4
63
1
Order By: Relevance
“…ADAM17 is a major sheddase for GPIb␣, 20 and the cytoplasm and ␣-granules of platelets contain MMP9. 45 The broad-range metalloproteinase inhibitor GM6001 preserved GPIb␣ expression on the surface of FlnA-null platelets stored 24 hours at 37°C, as did a selective MMP9 inhibitor (data not shown). How FlnA-null platelets increase ADAM17 and MMP9 expression and GPIb␣ cleavage is unclear.…”
Section: Org Frommentioning
confidence: 99%
“…ADAM17 is a major sheddase for GPIb␣, 20 and the cytoplasm and ␣-granules of platelets contain MMP9. 45 The broad-range metalloproteinase inhibitor GM6001 preserved GPIb␣ expression on the surface of FlnA-null platelets stored 24 hours at 37°C, as did a selective MMP9 inhibitor (data not shown). How FlnA-null platelets increase ADAM17 and MMP9 expression and GPIb␣ cleavage is unclear.…”
Section: Org Frommentioning
confidence: 99%
“…The sensitivity and specificity for predicting the likelihood of a donor being in the breast cancer group compared with the control group (no breast disease) was 78 and 89% respectively. While there may be questions and issues associated with the use of serum for measurement of MMPs because of their generally higher levels, 14,15 and the effects of preanalytical processing, [3][4][5] our results strongly suggest that there are still detectable differences in the MMP levels in serum that are apparently sufficient to allow distinction between different breast disease categories with statistical confidence. Our paper is important because it represents one of the few (if not the only one) to measure 4 MMP2 and 4 MMP9 variables in >300 serum samples collected from a population in which plasma has been analyzed.…”
mentioning
confidence: 66%
“…Oxidative stress can contribute to the activation of MMPs (10,12). Similar to oxidant-induced increases in MMP activity (13,14), we speculate that 100% reoxygenation (to a lesser extent, 21% reoxygenation) causes the activation and release of MMP-9, which contributes to platelet aggregatory dysfunction (8,9). The nonsignificant difference in MMP-9 activities between 100% and 21% reoxygenated groups may be related to the small number of animals used.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to MMP-2, MMP-9 inhibits platelet aggregation when released from platelets (8,9). We previously reported that the plasma MMP-9 activity was not different, whereas the plasma MMP-2 activity increased gradually over the first day of extracorporeal membrane oxygenation in critically ill newborns (26).…”
Section: Discussionmentioning
confidence: 99%